Knowledge, Attitudes, Impact, and Anxiety Regarding COVID-19 Infection Among the Public in China - Yulan Lin; Zhijian Hu; Haridah Alias; Li Ping Wong (Frontiers Media S.A., 2020)
Objectives: Sufficient knowledge and positive attitudes are crucial to the prevention of COVID-19. However, little is known about public awareness and attitudes regarding COVID-19 in China. The impact of COVID-19 on the societal well-being and anxiety levels of the public has never been documented. The aim of this study was to survey the knowledge, attitudes, impact, and anxiety levels of the people of China in relation to the COVID-19 outbreak.Method: A cross-sectional population survey using an online questionnaire was undertaken between Jan 24 and Feb 24, 2020. The study participants were residents of mainland China over the age of 18 years. The attitude items in this study measured the perceived threat of COVID-19 based on the Health Belief Model. Anxiety was measured with the State-Trait Anxiety Inventory (STAI), a self-reported questionnaire that measure both state (STAI-S), and trait anxiety (STAI-T)Results: A total of 2,446 completed responses were received. The mean and standard deviation (SD) for the total knowledge score was 20.3 (SD ± 2.9) out of a possible score of 23. The social disruption and household economic impact were notable, particularly in provinces with higher cumulative confirmed cases. The majority of responses indicated a low perceived susceptibility of being infected (86.7% [95%CI 85.4-88.1]), with a fair proportion of respondents perceiving a higher severity (62.9% [95% CI 61.0-64.8]). The mean total impact score was 9.9 (SD ± 3.8) out of a possible score of 15. The mean score for STAI-S was 48.7 (SD ± 10.8), whereas the mean STAI-T score was 45.7 (SD ± 8.5). By demographics, women reported significantly higher odds for higher levels of both STAI-S (OR = 1.67) and STAI-T (OR = 1.30) compared to men. People of a younger age were also more likely to experience higher STAI-S and STAI-T. Higher perceived susceptibility and severity and impact were strong predictors of higher levels of STAI-S and STAI-T.Conclusion: Our findings can assist in tailoring public communication to change people's knowledge and attitudes. The present study also underlined the importance of the promotion of mental health during infectious disease outbreaks to help in moderating the perceived threat, social and household economic impact, targeting the vulnerable segment of the population.